TYPOLOGICAL FEATURES OF LEISURE FACILITIES: UKRAINIAN AND FOREIGN EXPERIENCE - Григорчук, Г. В.; Абизов, В. А. (Art and Design, 2024)
Purpose: to determine the classification principles of modern leisure centres for further study and identify the features and principles of creating their harmonious internal architectural environment. Methodology. The research is based on the method of comprehensive analysis and synthesis of objective data obtained from open sources. The analytical part is based on materials from thematic publications, Internet resources, and the authors' personal experience. The methods of historical, comparative and typological analysis are used. Results. The typology of modern leisure centres has been generalised, systematised and defined, taking into account a wide range of features. Among them, the main ones are the following: by territorial and urban planning location; by location in the structure of buildings; by size; by purpose; by age; by form of ownership and sources of financing; by the nature of accessibility; by social aspect. The article provides examples of modern leisure centres in Ukraine and abroad, classified by type, taking into account their location and peculiarities of functional and planning structure. Scientific novelty. Due to the popularity of multifunctional leisure facilities in Ukraine, there is an objective need to create effective modern spaces in them that will meet the needs of all components of the institution. Such facilities can be considered as modern leisure centres in terms of their form and characteristics. The novelty of the study is to summarise the existing classification principles of leisure facilities and define the typology of modern leisure centres, taking into account a wide range of features. A deep understanding of the specifics of each type of leisure centre will allow to develop interiors of the appropriate functional-spatial and artistic-figurative organisation according to the accepted typology. Practical significance. The proposed typology of modern leisure centres can be the basis for further analytical and practical applications in the field of architectural environment design research. It will allow scientists and design professionals to implement the principles of optimal organisation of the interior space of modern leisure centres in order to achieve a harmonious and efficient environment. In addition, the results obtained can be applied in the practice of designing and operating modern leisure centres, contributing to the improvement of their functionality and comfort for users.